Progress in Cryptology – AFRICACRYPT 2019 - (:unkn) unknown (My University, 2019)
This book constitutes the refereed proceedings of the 11th International Conference on the Theory and Application of Cryptographic Techniques in Africa, AFRICACRYPT 2019, held in Rabat, Morocco, in July 2019. The 22 papers presented in this book were carefully reviewed and selected from 53 submissions. The papers are organized in topical sections on protocols; post-quantum cryptography; zero-knowledge; lattice based cryptography; new schemes and analysis; block ciphers; side-channel attacks and countermeasures; signatures. AFRICACRYPT is a major scientific event that seeks to advance and promote the field of cryptology on the African continent. The conference has systematically drawn some excellent contributions to the field. The conference has always been organized in cooperation with the International Association for Cryptologic Research (IACR).
Keywords: African Research